PALLIATIVE CARE IN PATIENTS WITH CHRONIC HEART FAILURE - Rodríguez-León, Amarelys (2022)
Palliative care is used to solve suff ering, restore the dignity of the person, and satisfy human needs. Th e majority of patients with Chronic Heart Failure are of advanced age and are not susceptible to heart transplantation, despite being a syndrome with high lethality and poor prognosis, the lack of comprehensive and eff ective palliative care is evident in studies that describe the end of the lives of patients. A descriptive cross-sectional study was carried out in 158 patients, with the aim of describing the sociodemographic characteristics and human needs of the patients according to their responses when integrating palliative care into Nursing care, in Remedios, Cuba, from 2016 to 2020. Th ey predominated the group of the elderly from 70 to 79 years old and the fi gure of women, with medium technical level, marital status, widows, and religious beliefs. Among the most aff ected needs are physical symptoms, changes in emotions, inadequate family support, and communication.